2015
DOI: 10.1007/s12182-015-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

On the feasibility of re-stimulation of shale wells

Abstract: As a result of advances in horizontal completions and multi-stage hydraulic fracturing, the U.S. has been able to economically develop several decades of worth of natural gas. However, a considerable concern has risen on the economic viability of shale gas development for reasons associated with the fast production declines as well as recent down-turns of natural gas prices besides rises in the costs of new technologies. Therefore, an economic analysis is required to investigate the profitability of the refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The well productivity usually decays very fast 8,9 4 requiring re-stimulation for maximum yield, a process which is not always straightforward and 5 effective. 4,10,11 In addition, a shale play may not always be productive with current technologies 6 available, despite the fact that it is known to host gas. 12, 13 7 The environmental impact of the shale gas is also still under investigation.…”
Section: Introduction 6mentioning
confidence: 99%
“…The well productivity usually decays very fast 8,9 4 requiring re-stimulation for maximum yield, a process which is not always straightforward and 5 effective. 4,10,11 In addition, a shale play may not always be productive with current technologies 6 available, despite the fact that it is known to host gas. 12, 13 7 The environmental impact of the shale gas is also still under investigation.…”
Section: Introduction 6mentioning
confidence: 99%
“…In both exploration and production of shale gas, brittleness and ductility of shale are important evaluation parameters as they are closely related to natural shale fracture (Ding et al 2012), artificial hydraulic fracturing , drilling (Eshkalak et al 2015;Zeng et al 2015), permeability (Ghanizadeh et al 2013) and gas preservation (Yarali and Kahraman 2011;Gale et al 2014;Hu et al 2015;Liu and Sun 2015;Zeng et al 2015). Brittleness is one of the most important mechanical parameters of unconventional gas shale reservoir estimation when it comes to hydraulic fracturing (Gasparrini et al 2014;Holt et al 2015) and borehole wall stability assessment and gas preservation risk (Ingram and Urai 1999;Hu et al 2014;Zhou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Restimulation of hydraulic fracturing wells in deep shale formations using CO 2 is a promising technique to access the residual hydrocarbon after initial production has ceased to yield viable output [Eshkalak et al, 2015]. However, the leftover brine from the initial fracturing procedure is immiscible with both CO 2 and the residual hydrocarbon and might inhibit mobilization and extraction in the system.…”
Section: Introductionmentioning
confidence: 99%
“…However, current fracking practices are incredibly inefficient leaving up to 70% of the hydrocarbon behind [McGlade et al, 2013]. A recent study demonstrated the economic benefits of the restimulation treatments, including refracturing [Eshkalak et al, 2015]. This presents an opportunity to restimulate existing wells in order to enhance hydrocarbon production, thus extending their life and reducing the need for additional wells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation